The effect of an aerobic exercise program on the quality of life in children with cancer - Ezzat Khodashenas; Zahra Badiee; Mehdi Sohrabi; Ali Ghassemi; Vahideh Hosseinzade (The Turkish Journal of Pediatrics)
Aerobic exercise such as physical activity plays an essential role for a healthy development for children undergoing chemotherapy and radiation therapy. The aim of this study was to examine the effectiveness of an aerobic exercise program on quality of life in children undergoing cancer treatment. Patients diagnosed with acute lymphoblastic leukemia (ALL), undergoing chemotherapy, were divided into two groups; the control group received the routine treatment with activities of daily living and the interventional group received routine treatment in addition to an aerobic exercise program. Data was collected using the pediatric quality of life questionnaires (PedsQL version 4) before and after the training program. We enrolled 20 cancer patients, who were referred to Dr. Sheikh Children`s Hospital in Mashhad, Iran; 8 (40%) and 12 (60%) of the patients were female and male, respectively. The results show a significant association in the pain and injury subscale (p=0.002), improving in interventional groups after test compared to the control groups. The reports of parents of the children`s quality of life showed significant association in the pain and injury subscale (P=0.002), and cognitive problems subscale at school (P=0.039). The regular exercise and psychosocial program intervention can improve wellbeing and thereby enhance efficacy of the children during treatment.